Os efeitos da interação com a organização-cliente, na subjetividade do consultor organizacional - Borgo, Ana Silvia Alves (2018)
In the current socioeconomic scenario with high unemployment rates, employed workers live with the fear of losing it. To reduce this fear, they put their best efforts to meet the organization’s demands of improving their performance, striving in different ways, as of updating and developing new skills to increase self-productivity. Facing this pressure, these workers ’mental and physical health will not be uninjured, whether due to a mental or somatic illness or an enigmatic normality in situations of apparent suffering. In this scenario, there’s also an increase in the number of workers with no formal employment relationship, who are therefore not "protected" by the Brazilian Consolidated Labor Laws or any statute of public institution. Among these workers is the organizational consultant, a professional activity, which has grown significantly in the market, usually as an alternative option to the unemployment. Named as autonomous or liberal professionals, their real practice does not fit this denomination, not preventing them from the pressure to keep their labour activity and its consequences for mental and somatic health, mainly the relation with the organizations which require their services. An integrated view for the psychism with the body, that proposes to investigate the enigmatic normality is the Work Psychodynamic approach, which was this research’s theoretical base in order to answer to the problem: what are the possible effects of the interaction with the client organization , in the organizational consultant subjectivity in his work, in spite of pleasure and suffering aspects? The analysis level was a group of professionals who act on people training and development, linked to companies from diverse segments. Data was collected through structured interviews and focus group. Data was collected through structured interviews and Focus Group and it was analyzed using content analysis according to Bauer (2002) procedures. It was verified that the organizational consultant in the relationship with the client organization has his/her subjectivity affected in pleasure experiences when he/she has the possibility to interfere in the work organization through creations which allow applying his/her experience and professional knowledge, the recognition of work utility also provides pleasure and contributes to build the social identity. The experiences of suffering are related to the work inconstancy, the uncertainty of payment for the services provided, the client’s control in a subordination relationship, the prescribed work that resembles a script, making him/her an executor instead of a consultant. Individual and collective defensive strategies became more evident in the Focus Group and presented in rationalization, denial, and normopathy forms. Somatization related to labor issues reported by some surveyed indicate the defensive strategies’ exhaustion. However, given the contributions of this professional to human and organizations development, it’s considered important to carry out studies to increase the knowledge about this object.